2021
DOI: 10.3389/fnins.2021.618589
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ulinastatin on Early Postoperative Cognitive Dysfunction in Elderly Patients Undergoing Surgery: A Systemic Review and Meta-Analysis

Abstract: Background: Postoperative cognitive dysfunction (POCD) is associated with neuroinflammation by triggering the systemic inflammatory responses. Related studies have demonstrated that ulinastatin, which is a urinary trypsin inhibitor, inhibited the release of inflammatory mediators and improved postoperative cognitive function in elderly patients undergoing major surgery. However, there are controversial results put forwarded by some studies. This systemic review aimed to evaluate the effect of ulinastatin on PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…POCD is the result of various mechanisms, such as neuroinflammation, oxidative stress, dysfunction of neurotransmitters or their receptors, circadian rhythm disorders, iron overload ( Gögenur et al, 2007 ; Li et al, 2016 ; Netto et al, 2018 ; Luo et al, 2019 ; Wang C. M. et al, 2021 ). At present, the drugs for the prevention and treatment of POCD include non-steroidal anti-inflammatory drugs (parecoxib, acetaminophen, ibuprofen), anesthesia-related drugs (dexmedetomidine, etomidate, oxycodone), ulinastatin, desferrioxamine, antipsychotics, and so on ( Zhou et al, 2019 ; Gan et al, 2020 ; Huang et al, 2020 ; Yu and Xie, 2020 ; Zhao et al, 2020 ; Duan et al, 2021 ). However, there is still a lack of safe and effective ideal drugs.…”
Section: Introductionmentioning
confidence: 99%
“…POCD is the result of various mechanisms, such as neuroinflammation, oxidative stress, dysfunction of neurotransmitters or their receptors, circadian rhythm disorders, iron overload ( Gögenur et al, 2007 ; Li et al, 2016 ; Netto et al, 2018 ; Luo et al, 2019 ; Wang C. M. et al, 2021 ). At present, the drugs for the prevention and treatment of POCD include non-steroidal anti-inflammatory drugs (parecoxib, acetaminophen, ibuprofen), anesthesia-related drugs (dexmedetomidine, etomidate, oxycodone), ulinastatin, desferrioxamine, antipsychotics, and so on ( Zhou et al, 2019 ; Gan et al, 2020 ; Huang et al, 2020 ; Yu and Xie, 2020 ; Zhao et al, 2020 ; Duan et al, 2021 ). However, there is still a lack of safe and effective ideal drugs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 24 ] Its diagnosis requires neuropsychological testing. [ 25 ] Herein, this experiment showed that LncRNA GAS5 raised cognitive impairment and increased neuroinflammation in mice model. Zhao et al suggests silencing GAS5 protects against brain injury in hypoxia/ischemia model.…”
Section: Discussionmentioning
confidence: 94%
“…Clinical studies and meta-analysis suggest that ulinastatin may attenuate POCD by reducing the release of TNF-α and IL-6 (Duan et al, 2021;Hirsch et al, 2016;Li et al, 2018;Lili et al, 2013). Ulinastatin reduces proinflammatory cytokine levels, such as TNF-α, CRP, and IL-6, by activating the PI3K/Akt/Nrf2 pathway (Li et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In view of the different incidence rates of POCD at different time points after operation, we performed summary statistics and metaanalyses on the occurrence of POCD on postoperative days 1, 3, and 7 (Duan et al, 2021;Huang et al, 2020a;Li et al, 2021a;Mansouri et al, 2019).…”
Section: Introductionmentioning
confidence: 99%